2021
DOI: 10.1186/s10194-021-01254-2
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral facial injection of Botulinum neurotoxin A attenuates bilateral trigeminal neuropathic pain and anxiety-like behaviors through inhibition of TLR2-mediated neuroinflammation in mice

Abstract: Objectives In this study, we investigated the possible analgesic effects of Botulinum toxin type A (BoNT/A) on trigeminal neuralgia (TN). A modified TN mouse model was established by chronic constriction injury of the distal infraorbital nerve (dIoN-CCI) in mice, and the possible roles of microglia toll-like receptor 2 (TLR2) and neuroinflammation was investigated. Methods Male C57BL/6 mice were divided into 3 groups, including sham group, vehicle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 61 publications
1
20
1
Order By: Relevance
“…Previous studies have suggested that TLR2 is involved in the pathogenesis of neuropathic pain and trigeminal neuralgia. However, the mechanism of TLR2 pathway during migraine attacks remains unclear [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that TLR2 is involved in the pathogenesis of neuropathic pain and trigeminal neuralgia. However, the mechanism of TLR2 pathway during migraine attacks remains unclear [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…TLRs are normally expressed in immune and glial cells of the CNS [39,40]. In addition to pathogen recognition, TLRs also function to recognize the molecular patterns of ligands associated with cellular stress, tissue damage, or cell death [41][42][43].…”
Section: Tlrs and Migrainementioning
confidence: 99%
“…The activation of CaMKII + neurons in the bilateral LHb may induce pain and anxiety via LHb regulation of the 5-HT, dopaminergic (Li et al, 2017;Metzger et al, 2021), and overall reward systems (Wang et al, 2017) given its complex network of nerve projections (Hetu et al, 2016;Browne et al, 2018). Although adult male C57BL/6 mice are frequently used in the study of TN and related emotions (Trevisan et al, 2016;Chen et al, 2021) and we also provided preliminary evidence demonstrating that the LHb plays an important role in the regulation of TN and related anxiety-like behaviors using these mice (Cui et al, 2020b), whether our findings differs according to species and sex requires further validation. This is an important topic that we are currently working on.…”
Section: Discussionmentioning
confidence: 99%
“…A study assessing the efficacy of BTX-A through inhibition of microglia toll-like receptor 2 (TLR2)-mediated neuroinflammation in mice demonstrated that BTX-A significantly inhibited microglia activation, thus demonstrating the mechanism behind the efficacy of BTX-A in TN. Subcutaneous unilateral injection of BTX-A in whisker pad attenuated the bilateral mechanical pain hypersensitivity and anxiety-like behaviors [ 32 ]. Another study involving rats showed that BTX-A when administered peripherally localized bilaterally in the trigeminal ganglia and demonstrated a role of axonal and hematogenous transport in the therapeutic role of BTX-A.…”
Section: Reviewmentioning
confidence: 99%